GDP mimicking portfolios and the cross-section of stock returns - Tim A. Kroencke; Felix Schindler; Steffen Sebastian; Erik Theissen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
The components of GDP (residential investment, durables, nondurables, equipment and software, and business structures) display a pronounced lead-lag structure. We investigate the implications of this lead-lag structure for the cross-section of asset returns. We find that the leading GDP components perform well in explaining the returns of 25 size and book-to-market portfolios and do reasonably well in explaining the returns of 10 momentum portfolios. The lagging components do a poor job at explaining the returns of 25 size and book-to-market portfolios but explain the return of momentum portfolios very well. A three-factor model with the market risk premium, one leading and one lagging GDP component compares very favorably with the Carhart four-factor model in jointly explaining the returns on 25 size/book-to-market portfolios, 10 momentum portfolios and 30 industry portfolios.
Keywords: E32; G12; 330; Business Cycle; Lead; Lag; Size; Value; Momentum